Policy inconsistency detection based on RBAC model in cross-organizational collaboration - Teo, Poh Kuang; Ibrahim, Hamidah; Sidi, Fatimah; Udzir, Nur Izura (Universiti Utara Malaysia Press, 2011)
Policy integration and conflict resolutions among various organizations still remain a major challenge. Moreover, policy inconsistency detection approach with logical reasoning techniques which considers integration requirements from collaboration parties has not been well studied. In this paper, we proposed a model to detect inconsistencies based on role-based access control (RBAC) that considers role hierarchy (RH) and temporal and spatial constraints. A model to prune and collect only the required policies based on access control requirements from different organizations is designed. Policy inconsistency detection should be enhanced with logical-based analysis in order to develop security policy integration. We believe this work could provide manner to filter a large amount of unrelated policies and only return potential collaboration policies for conflict resolution.